2010
DOI: 10.2105/ajph.2009.170464
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Retail Density and Demographic Predictors of Health Disparities: A Geographic Analysis

Abstract: Objectives We examined whether the geographic density of alcohol retailers was greater in geographic areas with higher levels of demographic characteristics that predict health disparities. Methods We obtained the locations of all alcohol retailers in the continental United States and created a map depicting alcohol retail outlet density at the US Census tract level. US Census data provided tract-level measures of poverty, education, crowding, and race/ethnicity. We used multiple linear regression to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
68
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 17 publications
4
68
2
Order By: Relevance
“…The local availability of tobacco, alcohol and food is especially relevant and worth assessing in the investigation of place effects on health (12) . In fact, some studies have previously shown a positive correlation between neighbourhood deprivation and the availability of tobacco (13)(14)(15)(16)(17)(18) , alcohol (4,19,20) as well as convenience and fast foods (18,(21)(22)(23)(24) .…”
mentioning
confidence: 99%
“…The local availability of tobacco, alcohol and food is especially relevant and worth assessing in the investigation of place effects on health (12) . In fact, some studies have previously shown a positive correlation between neighbourhood deprivation and the availability of tobacco (13)(14)(15)(16)(17)(18) , alcohol (4,19,20) as well as convenience and fast foods (18,(21)(22)(23)(24) .…”
mentioning
confidence: 99%
“…States with higher proportions of Black and Hispanic residents have greater concentrations of alcohol outlets (Berke et al, 2010;Gorman & Speer, 1997;LaVeist & Wallace Jr., 2000;Romley et al, 2007). This observation is highly relevant to public health because there is considerable evidence that problems such as intentional injuries (Cunradi et al, 2012;Gruenewald & Remer, 2006;Livingston, 2008Livingston, , 2011Mair et al, 2013;Toomey et al, 2012), road trauma (McMillan et al, 2007;Ponicki et al, 2013), and child abuse and neglect (Freisthler & Weiss, 2008;Freisthler et al, 2007) occur more frequently in areas with more alcohol outlets (Campbell et al, 2009).…”
Section: P Revious Studies Have Found That Areas In the Unitedmentioning
confidence: 99%
“…However, these studies contain a number of key limitations, and theory regarding the spatial dynamics of retail markets predicts that Black and Hispanic groups will in fact have fewer outlets near their residences because these populations consume less alcohol. In that context, this study examined the claim that excess exposure to alcohol outlets is an issue of environmental justice for racial and ethnic minorities (Berke et al, 2010;LaVeist & Wallace Jr., 2000;Romley et al, 2007).…”
Section: P Revious Studies Have Found That Areas In the Unitedmentioning
confidence: 99%
See 2 more Smart Citations